Self-assessment of vocational preparation and plans regarding undertaking employment among bachelor degree physiotherapy students of university-level schools of different educational orientations - Gotlib, Joanna; Prokopowicz, Katarzyna; Płaszewski, Maciej; Nowotny-Czupryna, Olga; Majcher, Piotr; Kułak, Wojciech; Grzegorczyk, Joanna; Bauer, Aleksandra; Barczyk, Katarzyna; Cabak, Anna; Białoszewski, Dariusz; Sierdziński, Janusz (Polish Journal of Public Health, 2010)
Introduction. A major change resulting from the separation of Bachelor- and Master-level studies is that after the completion of the Bachelor-level programme the student obtains a diploma of higher vocational education, i.e. a Bachelor’s degree, and becomes certified to practice the chosen profession. Aim. The objective of this study was to analyse the self-assessment of vocational preparation and vocational plans among physiotherapy students during their Bachelor programme studies at university-level schools of different educational orientations and compare self-ratings expressed by students of medical universities (MS), universities of physical education (PE), and other university-level schools (OU) during the first and third year of their Bachelor’s programme. Material and methods. The study involved the total of 593 students of 10 Polish universities (4 MS, 2 PE and 4 OU). The study was carried out in March and April 2009 among third-year students. The participation was voluntary. The data collected were the responses to an 88-question anonymous questionnaire designed by the authors. Statistical analyses utilised the chi-squared test (χ2) and the Kruskall-Wallis test at p